The total sound power radiated by a clamped-guided annular plate excited for vibrations by an external surface pressure - Rdzanek, W. P.; Zawieska, W. M. (Archives of Acoustics, 2004)
A problem of sound radiation by a clamped-guided annular plate with a hole in its center has been considered which is considerably more complex than it is in the case of a circular plate. The plate is subjected for vibrations by an external pressure. The vibrating system is controlled by a shaker clamped into the internal edge of the plate which make it possible to control vibrations of the plate as well as the total sound power radiated. The plate's volume displacement has been presented which make it possible to roughly rate the compensation quality. An amplitude-phase compensation system make it possible to observe both resonance and antiresonance phenomenas.